Analisis Forensik Konten Satir Politik: Studi Kasus Unggahan Meme Prabowo pada Akun Instagram @kegobloganunfaedah Tanggal 8 Desember: Forensic Analysis of Political Satire Content: A Case Study of the Prabowo Meme Posted on Instagram Account @kegobloganunfaedah on 8th December - Deanovan Anggraeni; Nur Lailiyah (Universitas Tidar, 2026)
This study aims to analyze netizens' speech on political meme uploads of Prabowo on the Instagram account @kegobloganunfaedah using a forensic linguistic approach, and examine its implications for the provisions of Article 27 paragraph (3) of the ITE Law regarding insults and defamation. The theoretical basis used focuses on political satire, including irony, sarcasm, humor, criticism, and indirectness in conveying opinions. The research method applied is descriptive qualitative with data collection techniques through digital observation, listening, and taking notes, 25 selected comment samples were analyzed in depth. The results of the study show that people use various satirical language strategies to express political criticism, but some comments have the potential to violate the law because they contain elements of insults or defamation. This study emphasizes the need for legal awareness in the use of social media, as well as the importance of understanding the limits of freedom of expression to remain legally valid